The impact of urban expansion on food production: a bibliometric study of development, hotspots, and future prospects - Cao, Congjie; Wang, Jiayu (Frontiers in Sustainable Food Systems, 2025)
The acceleration of urban expansion and rapid economic growth have significantly intensified agricultural land scarcity, jeopardizing global food security. Although this issue has become a key topic in global food security, a comprehensive and systematic literature review is still lacking. To systematically analyze the evolutionary patterns, research frontiers, and knowledge structure in this field, this study employs an integrated bibliometric approach using CiteSpace, VOSviewer, and Bibliometrix R-tool for comprehensive knowledge mapping. The results indicate that research on the impact of urban expansion on food production can be divided into an initial period (1983–1999), a period of rapid development (2000–2014), and a period of high growth (2015–present). One hundred thirty-nine countries have conducted research in this area. Research on greenhouse gases, simulation forecasting, carbon footprints, and smart agriculture has emerged as hotspots in this field in recent years. Crop yield, land use change, and food security have consistently been central research themes. This study also highlights future research directions, emphasizing the importance of interdisciplinary collaboration, scenario-based analysis, and methodological advancements in bibliometric studies. Balancing economic development with food production amid urbanization remains a critical challenge that warrants further exploration. Additionally, key limitations, such as database constraints and potential analytical biases, are discussed. These findings may serve as a valuable reference for future research in this domain.